The Influence of Substrate Preparation on the Performance of Two Alkyd Coatings After 7 Years of Exposure in Outdoor Conditions - Beldean, Emanuela Carmen; Timar, Maria Cristina; Manea, Emilia-Adela Salca (MDPI AG, 2025)
Alkyd resins are among the most common coatings used for exterior wood joinery. In Romania, solvent-borne alkyd coatings are widely used to finish wood. The study aims to compare the performance after 7 years of outdoor exposure of two types of alkyd coatings, a semi-transparent brown stain with micronized pigments (Alk1) and an opaque white enamel (Alk2), applied directly on wood or wood pre-treated with three types of resins: acryl-polyurethane (R1), epoxy (R2), and alkyd-polyurethane (R3). Fir (Abies alba) wood served as the substrate. Cracking, coating adhesion, and biological degradation were periodically assessed through visual inspection and microscopy. Additionally, a cross-cut test was performed, and the loss of coating on the directly exposed upper faces was measured using ImageJ. The results indicated that resin pretreatments somewhat reduced cracking but negatively affected coating adhesion after long-term exposure. All samples pretreated with resins and coated with Alk1 lost more than 50% (up to 78%) of the original finishing film by the end of the test. In comparison, coated control samples lost less than 50%. The Alk2 coating exhibited a film loss between 2% and 12%, compared to an average loss of 9% for the coated control. Overall, samples pretreated with alkyd-polyurethane resin (R3) and coated with alkyd enamel (Alk2) demonstrated the best performance in terms of cracking, adhesion, and discoloration.
Keywords: alkyd coatings; resin pre-treatments; outdoors; adherence; fir